A bibliometric analysis of immunotherapy for atherosclerosis: trends and hotspots prediction - Wang, Jing-Hui; Pan, Guan-Rui; Jiang, Long (Frontiers in Immunology, 2024)
IntroductionAn increasing number of studies have demonstrated that immunotherapy may play a significant role in treating Atherosclerosis and has emerged as a promising therapy in this field. The aim of this study is to provide a comprehensive perspective through bibliometric analysis and investigate the existing hotspots and frontiers.MethodsThis study searched records from Web of Science, PubMed, and Scopus from January 1, 1999, to May 27, 2023. By using bibliometric software CiteSpace (6.3.R1) and VOSviewer (1.6.19), co-occurrence analysis was used to count the frequency of co-occurrence of certain elements (e.g., countries, regions, institutions, etc.), cluster analysis was used to classify keywords, and burst analysis was used to identify research trends and hotspots.ResultsThe results showed that the number of annual publications has grown in a fluctuating manner; the USA, China, and the Netherlands have the highest numbers of publications, and the top three institutions are located in the Netherlands, Sweden, and the USA. In addition, Nilsson J published the highest number of papers; Ridker PM and his article “Anti-inflammatory Therapy with Canakinumab for Atherosclerotic Disease” have played prominent roles. The top four Journals with the highest numbers of publications are “Arteriosclerosis Thrombosis and Vascular Biology”, “Frontiers in Cardiovascular Medicine”, “Circulation” and “Vaccine”. In addition, keyword analysis indicates that inflammation, nanoparticles, adverse events associated with immune checkpoint inhibitors, T cells and tumor necrosis factor will be future research hotspots.DiscussionThis study provides a comprehensive bibliometric analysis of immunotherapy in atherosclerosis, offering insights that advance scientific understanding. It not only assists researchers in grasping the current hotspots in this field but also reveals potential directions for future investigation. Moreover, future studies can optimize immunotherapy strategies based on hotspot predictions to decelerate the progression of atherosclerosis.